Students’ Enthusiasm in Learning English by Using Blended Learning - Indah Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to analyze students’ enthusiasm for English learning by using blended learning. This study was conducted by using descriptive qualitative and administered questionnaires. The subjects of this study were 70 students and this study applied Miles, Huberman, and Saldana’s steps in analyzing the data. The results showed that the students had a great enthusiasm for English learning by using blended learning which was indicated by their involvement, participation, task submission, and enjoyment of discussion during English learning